FRI0524 Juvenile Dermatomyositis (DM) with Normal Creatine Kinase. (9th June 2015) - Timpone, L.; Forni, C.; Fontana, F.; Orlando, F.; Brin, C.; Alessio, M.
Abstract : Background: Juvenile dermatomyositis (JDM) is the most frequent idiopathic inflammatory myopathy, characterized by vasculopathy of the skin and/or muscles causing symmetrical proximal weakness and typical skin rashes. In 1975 Bohan and Peter published a classification for dermatomyositis: a certain diagnosis can be obtained with the presence of typical exanthema and at least 3 of the following signs or symptoms: proximal symmetric muscle weakness, elevation of creatine kinase (CK), muscle biopsy and electroneuromyography. Objectives: To suggest it is useful to follow less specific muscle enzymes, such as aldolase, in JDM and normal CPK levels. Methods: We reviewed 22 patients (8 males and 14 females, median age 8, 2 years), with the diagnosis of JDG based on Bohan and Peter criteria. Skin signs preceded muscle manifestations in 7 patients (33%). The diseases was monophasic in 12 (57%) and polyphasic in 9 (43%) patients; one patient was lost at follow up; one patient died of cerebral hemorragia and another patient died of macrophagic activation syndrome. In all patient muscle enzymes were dosed: CK, aspartate amynotraspherase (AST), lactic dehydrogenase (LDH) and aldolase. Results: 5/22 (23%, 2 males and 3 females) patients had normal CK: at the beginning 2 of them presented muscle sympthoms (weakness, myalgia, walking difficulty) and cutaneous signs; 3 presented only cutaneous signs. In 3 of 4 patients was observed isolated alteration of aldolase and one of them was affected by a severe hepatic disease with cholestasis (elevated gamma glutamyl transferase). In 1 of them JDM was diagnosed on the basis of cutaneous and muscle signs and symptoms, elevated aldolase ad muscle alteration on magnetic resonance (negative muscle biopsy and electroneuromyography). From literature we know that in 5-10% cases of JDM can be found normal levels of CK. In our cohort 20% of patients with early muscle symptoms has normal CK levels and in 10% normal muscle enzymes. Conclusions: The use of aldolase compared with CK in muscle disorders is debated: aldolase can be altered in different diseases, such as erythrocyte diseases or hepatic disorders. CK can be negative because of the presence of inhibitors released by damaged muscle cells, muscle atrophy in advanced stages, concomitant hepatopathy or connective tissue diseases, steroid therapy or elevated acid uric and cystine levels that interfere with enzyme dosage. In suspicious cases of JDM it is useful to combine different enzymes to increase the diagnostic sensibility of this tests, associated with instrumental investigations if one them results negative. References: Carter JD, Kanik KS, Vasey FB. Dermatomyositis with Normal Creatine Kinase and Elevated Aldolase Levels. J Rheumatol 2001;28;2366-2367 Gowdie PJ, Allen RC, Kornberg AJ, Akikusa JD. Clinical features and disease course of patients with juvenile dermatomyositis. Int J Rheum Dis. 2013 Oct;16(5):561-7. doi: 10.1111/1756-185X.12107. Epub 2013 Jun 3. Disclosure of Interest: None declared